COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN WISATA DANAU MESJID KOTO KARI KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Hanifah, Aulia; Wasillah, Asiah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Koto Kari Mosque Lake tourist attraction is a new destination opened in 2016 and managed by the village together with tourism awareness groups and the private sector under the Mata Air Berkah Village-Owned Enterprise (BUMDes) since 2020. However, its management still faces limitations, both from the BUMDes and the community, requiring support from the Tourism and Creative Economy Agency (Pordakwis), the village government, and the Tourism Office. Development issues include destination management, marketing, institutions, and the creative economy. The purpose of this study is to describe collaborative governance and the inhibiting factors of the local government and village government in the development of the Koto Kari Mosque Lake tourist attraction in Kuantan Singingi Regency in 2021. This study uses a qualitative approach conducted in Koto Kari Village, Kuantan Tengah District, Kuantan Singingi Regency. The data used consists of primary and secondary data. Data collection techniques were carried out through interviews and documentation to obtain relevant information in the development of the Koto Kari Mosque Lake tourist attraction. The results of the study indicate that the implementation of collaborative governance in the development of the Koto Kari Mosque Lake tourist attraction has been running but is not yet optimal. Collaboration between stakeholders has not been supported by regular dialogue and consistent commitment. Inhibiting factors include the lack of a structured meeting schedule, weak agreements on business relocation, limited institutional capacity, and the absence of an integrated monitoring system. Keywords: Collaborative Governance, Tourism Development, Koto Kari Mosque Lake